The role of music in Ken Bugul’s novels - Sacharewicz, Edyta (Literatūra, 2019)
The analysis of the place that music occupies in the works of Ken Bugul is the main purpose of this article. The author will try to present how this art manifests in her novels paying attention to the unique character of literary language. The rhythm, the intensity, the repetitions that appear in the Bugul’s texts become inseparables elements of her creation and show the musicality of her work.
Keywords: literature; music; Ken Bugul; literary language